Application of Multidimensional Correspondence Analysis in the Research on the Quality of Natural Environment in Poland in 2007 - Bąk, Iwona (Zastosowanie wielowymiarowej analizy korespondencji do badania jakości środowiska naturalnego w Polsce w roku 2007, 2009)
The article attempts to answer a question of what kind of quality the natural environment was in Polish provinces in 2007 with reference to an average level of chosen variables that characterize the environment. The chosen variables describe the degree of air, water and soil pollution and inform about the environment protection expenditure incurred in the provinces and about remarkable natural virtues of the analyzed area.The main aim of the study was to indicate which provinces diverge in plus or in minus from the average level of chosen variables that characterize the quality of natural environment in Poland. Also, what kind of connections there are between the provinces with reference to the variables analyzed. A multidimensional correspondence analysis was used as a research tool based on a built complex matrix of markers. With respect to a large number of versions of analyzed variables the Ward method was used, which allows for identifying connections between the variants of variables.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 84, s. 49-56
Keywords: multiple correspondence analysis; natural environment; Ward method; indicator matrix